Ethics of prayer and work in 1 and 2 Thessalonians - Loba-Mkole, Jean-Claude (HTS teologiese studies, 2013)
This article raises the question of the balance between prayer and work. This topic is discussed through an intercultural approach of Paul’s recommendation about praying and working without ceasing (1 Th 1:9; 3:10). The main hypothesis postulates that constant prayer and work are associated with the concepts of thanksgiving (words of the εὐχαριστ-lemma) and exemplarity. It is argued that Pauline recommendations about praying and working without ceasing prove to be supported not only by an original biblical culture, but also by a church culture as well as a currently emerging African culture.